2014
DOI: 10.3892/or.2014.3068
|View full text |Cite
|
Sign up to set email alerts
|

Thioridazine, an antipsychotic drug, elicits potent antitumor effects in gastric cancer

Abstract: Abstract. Thioridazine, an antipsychotic drug, has been reported to induce apoptosis in various types of cancer cells, with specificity on targeting cancer stem cells (CSCs). However, whether it elicits anticancer effects in gastric cancer has never been reported. In the present study, we examined the ability of thioridazine to induce cell death in the gastric cancer cell lines NCI-N87 and AGS, and detected its in vivo tumor inhibition capacity. Thioridazine elicited cytotoxic effects on NCI-N87 and AGS cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 21 publications
(34 reference statements)
2
52
1
Order By: Relevance
“…Thioridazine has shown anti-angiogenic effects and apoptosis-inducing abilities in breast and ovarian cancer (20,21). It also induced cell death in cervical and gastric cancer (22,23). These findings indicate that DRD2 may be involved in cancer progression, and that its expression may be correlated with cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thioridazine has shown anti-angiogenic effects and apoptosis-inducing abilities in breast and ovarian cancer (20,21). It also induced cell death in cervical and gastric cancer (22,23). These findings indicate that DRD2 may be involved in cancer progression, and that its expression may be correlated with cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have suggested that antipsychotic drugs such as haloperidol, perphenazine, fluphenazine have anti-cancer effects. (17,40). Consistent with those studies, our results demonstrated the anti-metastatic effects of PF in breast cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Thioridazine (Thio), a phenothiazine derivative, is a piperidine antipsychotic drug that was recently found to inhibit cancer cell growth. [6][7][8] Doxorubicin (Dox), an anthracycline antibiotic, is one of the most widely applied anticancer drugs for various malignancies, including breast, prostate, and colon cancers. [9][10][11][12] However, serious side effects, such as the dose-dependent cardiotoxicity, myelosuppression, and nephrotoxicity, markedly limit its clinical use.…”
Section: Introductionmentioning
confidence: 99%